2010
DOI: 10.1080/10705422.2010.519682
|View full text |Cite
|
Sign up to set email alerts
|

Review and Analysis of the Benefits, Purposes, and Motivations Associated with Community Gardening in the United States

Abstract: Community gardens have been a part of modern American culture since the late 19th century. Participation in community gardening has ebbed and flowed in response to changing socioeconomic conditions, and thus the current economic recession has reheightened public interest. In a review of the scholarly literature from 1999 to 2010, rigorous quantitative research studies on the effects of community gardens are found to be sparse; however, a larger body of qualitative data is available. Eleven themes related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
180
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(196 citation statements)
references
References 53 publications
9
180
0
7
Order By: Relevance
“…This is reflected in the academic literature, where various case studies describe the extent of CGs in the cities of the Global North. While illustrating the environmental, social, and/or economic functions that CGs have for these cities, these case studies exemplify the multifunctionality of CGs and the various benefits and motivations associated with collective gardening (Draper & Freedman, 2010;Duchemin, Wegmuller, & Legault, 2008;Evers & Hodgson, 2011;Gittleman, Jordan, & Brelsford, 2012;Pourias, Daniel, & Aubry, 2012).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This is reflected in the academic literature, where various case studies describe the extent of CGs in the cities of the Global North. While illustrating the environmental, social, and/or economic functions that CGs have for these cities, these case studies exemplify the multifunctionality of CGs and the various benefits and motivations associated with collective gardening (Draper & Freedman, 2010;Duchemin, Wegmuller, & Legault, 2008;Evers & Hodgson, 2011;Gittleman, Jordan, & Brelsford, 2012;Pourias, Daniel, & Aubry, 2012).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…During the last decade, driven by the increasing popularity of CGs, several studies assessed the potential of CGs to contribute to the urban food supply (Darrot & Boudes, 2011;Grewal & Grewal, 2012;MacRae, Gallant, Patel, Michalak, Bunch & Schaffner, 2010;McClintock, Cooper, & Khandeshi, 2013). These studies concluded that a substantial part of urban food demand could be produced within the cities' own boundaries by putting vacant land into production.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In North-America and Europe, people participating in UA do so with a variety of motives [7][8][9][10]. As Veen [10] finds for the Netherlands, many people like to garden because they enjoy the act of gardening and not because they want to change the world or oppose the conventional food system.…”
Section: The Questionmentioning
confidence: 99%
“…Benefits of community gardens include better health, food source/food security, youth education, development, and employment, use and preservation of open space, crime prevention, neighbourhood beautification, leisure and outdoor recreation, cultural preservation and expression, social interactions/cultivation of relationships, stress relief, community empowerment, and mobilization (Armstrong, 2000;D'Abundo & Carden, 2008;Draper & Freedman, 2010;Ferris, Norman & Sempik, 2001;Kingsley, Townsen, & Henderson-Wilson, 2009;Van Den Berg & Custers, 2011). Gardens on university campuses in particular can address serious issues affecting students (e.g., nutritionally poor diets and food insecurity) (Chapparo et al, 2011;Hughes et al, 2011;Meldrum & Willows, 2006;Nugent, 2011).…”
Section: Introductionmentioning
confidence: 99%